2019
DOI: 10.1002/jmri.26628
|View full text |Cite
|
Sign up to set email alerts
|

MRI analysis of fecal volume and dryness: Validation study using an experimental oxycodone‐induced constipation model

Abstract: Background Opioids are known to affect gastrointestinal motility, but their effect on fluid absorption and secretion is poorly understood in humans. Purpose To investigate the effect of oxycodone on colonic fecal volume and stool dryness by using a novel MRI‐based technique. Study Type Prospective, randomized, double‐blinded, crossover study. Subjects Twenty‐five healthy male volunteers (median age: 24 years [range: 21–56]; mean body mass index [BMI]: 23.9 kg/m2 [range: 22.9–25.0]) without known gastrointestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The fact, that this was not observed in the other treatment arms, suggests that tapentadol may increase the water content compared to oxycodone. The water in colonic luminal content can be assessed using detailed analysis of MR images, which we previously have shown using both T2-weighted and DIXON-type water images [8]. However, our current data were sub-optimal for this analysis and image acquisition should be optimized in future studies so that information on the water in the colonic content can be further investigated.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The fact, that this was not observed in the other treatment arms, suggests that tapentadol may increase the water content compared to oxycodone. The water in colonic luminal content can be assessed using detailed analysis of MR images, which we previously have shown using both T2-weighted and DIXON-type water images [8]. However, our current data were sub-optimal for this analysis and image acquisition should be optimized in future studies so that information on the water in the colonic content can be further investigated.…”
Section: Discussionmentioning
confidence: 91%
“…The analgesic effect of tapentadol has been investigated in previous studies [5,6], however, its mechanic effect on colon function and how this interacts with gastrointestinal (GI) symptoms lacks evidence. It has previously been shown that magnetic resonance imaging (MRI) of segmental colorectal volumes provides an advantageous insight into colonic function, and how it can be affected due to diets or opioid treatment in healthy subjects [7,8]. The method has been found to have low inter-reader and day-to-day variability, high spatial resolution, and includes no contrast-enhancing agents or irradiation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Colon anatomy is well suited for 3D modeling of transit. A recent analysis has been utilized for classification of different motility patterns based on the velocity and length of magnetic capsule movements [2][3][4]. Insight into colonic motility offers many possibilities for classification of dysmotility symptoms or interventional testing of pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…If so, assessment of colonic volumes may allow clinicians to stratify patients and thereby guide treatment. In addition, future developments with postprocessing of MRI data will allow separation of colonic content into solid, fluid, and gas 32 . Such information may be important for evaluating individual patients and the effects of treatment or diet.…”
Section: Discussionmentioning
confidence: 99%